Novel therapeutic modulators of astrocytes for hydrocephalus - Yang, Yijian; Wang, Chuansen; Chen, Rui; Wang, Yuchang; Tan, Changwu; Liu, Jingping; Zhang, Qinghua; Xiao, Gelei (Frontiers in Molecular Neuroscience, 2022)
Hydrocephalus is a functional disorder of cerebrospinal fluid that causes ventricular dilation and intracranial hypertension. Astrocytes are the key response cells to the inflammation in the central nervous system. In hydrocephalus, astrocytes are activated and show a dual character depending on the period of development of the disease. They can suppress the disease in the early stage and may aggravate it in the late stage. More evidence suggests that therapeutics targeting astrocytes may be promising for hydrocephalus. In this review, based on the previous studies, we summarize different forms of hydrocephalus-induced astrocyte reactivity and the corresponding function of these responses in hydrocephalus and also discuss the therapeutic effects of astrocytes regulation on hydrocephalus in experimental studies.